Impact of Foreign Direct Investment, Human Capital, and Technology Transfer on Unemployment in Morocco: An Empirical Investigation - Chtioui, Nor-Eddine; Boushib, Kaoutar (International Journal of Economics and Financial Issues, 2025)
Previous studies have generally analyzed the impact of foreign direct investment (FDI), human capital and technology transfer on employment separately, without necessarily integrating them into a single model. This article aims to examine their combined effects on unemployment reduction in Morocco for the period between1990 and 2023 within the same model. The empirical approach, based on a staggered lag autoregressive econometric model (ARDL), reveals that in the long term, human capital development and FDI will play a fundamental role in reducing unemployment in Morocco, while the impact of technology transfer is not significant. In the short term, improving human capital has the strongest, most immediate and significant effects on reducing unemployment, followed by FDI and then technology transfer. In light of our results, we recommend that the Moroccan authorities adopt integrated policies aimed at simultaneously strengthening human capital development, attracting FDI and promoting technology transfer. Such an approach would make it possible to sustainably reduce unemployment and improve inclusive, sustainable economic development in Morocco.